Defects in the COG complex and COG-related trafficking regulators affect neuronal Golgi function - Climer, Leslie K.; Dobretsov, Maxim; Lupashin, Vladimir (Frontiers in Neuroscience, 2015)
The Conserved Oligomeric Golgi (COG) complex is an evolutionarily conserved hetero-octameric protein complex that has been proposed to organize vesicle tethering at the Golgi apparatus. Defects in seven of the eight COG subunits are linked to Congenital Disorders of Glycosylation (CDG)-type II, a family of rare diseases involving misregulation of protein glycosylation, alterations in Golgi structure, variations in retrograde trafficking through the Golgi and system-wide clinical pathologies. A troublesome aspect of these diseases are the neurological pathologies such as low IQ, microcephaly and cerebellar atrophy. The essential function of the COG complex is dependent upon interactions with other components of trafficking machinery, such as Rab-GTPases and SNAREs. COG-interacting Rabs and SNAREs have been implicated in neurodegenerative diseases like Alzheimer’s disease and Parkinson’s disease. Defects in Golgi maintenance disrupts trafficking and processing of essential proteins, frequently associated with and contributing to compromised neuron function and human disease. Despite the recent advances in molecular neuroscience, the subcellular bases for most neurodegenerative diseases are poorly understood. This article gives an overview of the potential contributions of the COG complex and its Rab and SNARE partners in the pathogenesis of different neurodegenerative disorders.